The used of ureolytic and sulphate reduction bacteria to improve properties and self-healing of concrete - Abdulaziz Al-Shalif, Abdullah Faisal (2016)
Concrete is the most widely used in construction materials but plain concrete is porous, low in tensile strength and prone to crack. Recent development in concrete technology had invented a new technology namely bio-concrete. This study investigated the used of ureolytic bacteria UB and sulphate reduction bacteria (SRB) in improving concrete properties and producing self healing. UB and SRB were isolated from fresh urine and acid mine water respectively. Both bacteria were simulated in alkaline and anaerobic conditions during isolation process for ensuring their survival in concrete. Both bacteria were casted in 1%, 3% and 5% as water replacement in concrete mix. Physical and mechanical properties test namely, compressive strength, splitting tensile strength, water penetration and carbonation were conducted. Self healing process was proven using scanning electronic microscopy with energy dispersive X-ray (SEM-EDX). The result showed that both UB and SRB are gram positive bacteria with coccus shape. The best performance observed with replacement ratio of 3% and 5% for UB and SRB respectively. Overall result of physical and mechanical properties showed that UB performed better than SRB. The addition of UB improve compressive strength, splitting tensile strength and reduce water penetration with the value of 23%, 14.2% and 10.34% respectively at 28 days. Furthermore, UB reduce carbonation depth with the value of 70% at 90 days. In the case of SRB, at 28 days the improvement are 13%, 10.7% and 8.5% for compressive strength, splitting tensile strength and water penetration respectively. Also, SRB reduce the carbonation depth with value of 60% at 90 days. SEM results showed the decrement of concrete pores size and coccus shape of the bacteria in concrete specimens. EDX results showed the increased of calcium content for both UB and SRB. This scenario proved the precipitation of calcium in bio-concrete. The statement above clear proved the ability of both UB and SRB improve concrete properties and self healing process.